A probabilistic study of monsoon daily rainfall at Calcutta by Markovian model and trend of rainfall during monsoon season (MAUSAM, 2001)
One-step transitional probability matrices are obtained by Markovian model from one transitional state to other for different rainfall characteristics (such as, non-rainy days, light rains, moderate rains, heavy rains and very heavy rains) at Calcutta (Alipore) for different monsoon months. The disorderness (unvertainty) of the transitional system of the monsoon rainfall characteristics are studied by Shannon’s model. The favourable or unfavourable condition of different states are also studied by redundancy test during monsoon period at Caluctta. A Long-run probability vectors of such rainfall characteristics are found out from probability matrices. A trend in rainfall amounts during monsoon period at Calcutta for each of the monsoon month, June to September, has also been studied here.